Improvement of solid particle erosion resistance of helicopter rotor blade with hybrid composite shield. (March 2021) - Özen, İsmail and Gedikli, Hasan and Öztürk, Bülent
Highlights: GF/EP and CF/EP composites suffered more severe erosion than SS304 and Ni materials. CFD achieved great advantages in modeling erosion damage on a curved shield surface. PU tape material provided better erosion resistance than GF/EP and CF/EP composites. Hybrid shield with PU tape improved erosion resistance of helicopter rotor blades. Abstract: In the present study, the solid particle erosion behavior of polyurethane (PU) tape (3M-8663) material, bidirectional carbon fiber reinforced epoxy (CF/EP) and glass fiber reinforced epoxy (GF/EP) composites has been characterized experimentally and numerically. In the experimental part, steady-state erosion rates of aforementioned materials have been evaluated at different impact angles (20°, 30°, 45°, 60°, and 90°) and different impact velocities (70, 110, 150, and 190 m/s), and compared with those of stainless steel (SS304) and pure nickel materials (Ni) which are commonly used for erosion shield of helicopter rotor blades. Tests were conducted at room temperature using silica (SiC) particles (average diameter of 175 µm) as an erodent. Erosion behaviors on the shield surface of the same materials were investigated numerically under different impact velocities (110, 150, 190, and 230 m/s) for a pitch angle of 0°. Numerical erosion simulations were realized with commercial ANSYS-Fluent software using the finite volume method, an erosion model, and a discrete phase method with the Eulerian-Lagrangian approach. The experimental results showed that the GF/EP and the CF/EP composites indicated the maximum erosion rate at the impact angles ranged from 60° to 90°, whereas the PU tape material exhibited the maximum erosion rate at the impact angle of 30°. The results also showed that the PU tape surface clearly provided much better erosion resistance than the GF/EP and CF/EP composite surfaces, and the hybrid erosion shield having the PU/SS304 surface significantly improved the erosion resistance of the helicopter rotor blade up to the impact velocity of 150 m/s. A good agreement was also observed between the experimental and the numerical results.